Methods for Distalizing Molar – A Review - B Raghavendra1 , E.thulasi Ram2 , Harini R1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The extraction or non extraction debate from the Angle era to the present day orthodontics does not definean absolute indication for a specific treatment plan One of the non-compliance therapies and fairly recentconcept is the MOLAR DISTALIZATIONwhich has been effectively used in the correction of malocclusion.Advances in mechanotherapy and changes in treatment concepts have reduced or minimized the need forextraction in severe discrepancies. Various techniques are currently employed in non-extraction therapy inthe treatment of a malocclusion